CDEM-Based Numerical Simulation of Uniaxial Compressive Mechanical Properties of Rocks - Mingming Liu; Zhiyong Song; Shou Ma; Yuhua Wei; Jingrui Wang (Advances in Civil Engineering)
Understanding the mechanical properties of rock is of great significance for the development of unconventional reservoirs. However, a large number of bedding makes the mechanical laws of rock unclear. To investigate the effect of bedding properties on the uniaxial mechanical properties of rock, the coal model containing bedding is developed based on the continuous–discontinuous method, and the effect of bedding angle, bedding strength, bedding number, and loading rate on the uniaxial mechanical properties of rock is investigated. The failure morphology, stress–strain evolution, peak stress, and fracture degrees are analyzed and discussed in detail. The reliability of the numerical model in this paper has been verified by comparison with the indoor experiments. The results show that when the bedding angle is 0°, the peak stress of the rock is maximum, 8.16 MPa, and when the bedding angle is 90°, the fracture degree of the rock is maximum, 3.74%. For the different bedding strengths, the peak stress first decreases linearly with the decrease of the bedding strength. The peak stress barely varies when the bedding strength is less than 0.5 MPa. The fracture degree of the rock shows a nonlinear increase with the increase in bedding strength. For different bedding numbers, the activation of the bedding is not related to the bedding number. The loading speed also has a great influence on the mechanical properties of rock. With the increase in loading rate, the difficulty of bedding activation gradually increases, and the complexity of fractures gradually increases. This study aims to further improve the understanding of the effect of bedding properties on the uniaxial mechanical properties of rock.